Effect of Student Teamss Achievement Division (STAD) on Mathematical Learning Results in SDLB Surabaya - Agustini, Lia (International Journal for Educational and Vocational Studies, 2019)
Researcher's applied Student Teams Achievement Division (STAD) with the goals students' learning skills in elementary schools, Majesty I Surabaya. The approach used in this research is quantitative. The research was pre experiment. The design used the one group pre test and post test. The method was tested, to collect data from mathematic learning results before and after giving intervention. The application of intervention was conducted 10 times meeting with the time allocation 60 minutes each meeting. The data analysis used is a non parametric statistic, a sign test. The analysis result was used to sign a test that could be concluded that there was a significant influence using Student Team Achievement Division (STAD) toward student learning in SDLB-B Noble work I Surabaya with ZH value = 2, 05 > Z table 5% 1, 96.